Al-Taqdim wa al-Ta'khir: Linguistic Rules in Qur'anic Interpretation - Wardah, Lailatul; Fikri, Syarifuddin Ala Dzil (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
This study examines the linguistic concept of Al-Taqdim wa al-Ta’khir in Qur’anic interpretation, focusing on its influence on meaning construction. Al-Taqdim wa al-Ta’khir are fundamental principles in Arabic syntax that affect the arrangement of words in a sentence, where Al-Taqdim refers to advancing a word in order, and Al-Ta’khir refers to delaying it. These principles play a crucial role in shaping the meaning of Qur’anic verses and influencing exegetical interpretations. The study aims to analyze how Al-Taqdim wa al-Ta’khir functions in Qur’anic exegesis and how it assists mufassirs (exegetes) in navigating linguistic complexities within the sacred text. This research employs a qualitative library-based method with a descriptive-analytic approach. The study is conducted in two stages: a deductive phase, where existing literature on Al-Taqdim wa al-Ta’khir is examined broadly, and an inductive phase, where relevant examples from Qur’anic verses are analyzed to determine the interpretive effects of word order shifts. The findings indicate that Al-Taqdim wa al-Ta’khir significantly impacts both memorization and meaning in Qur’anic exegesis. Word order changes can either enhance rhetorical beauty and clarity or create ambiguity if not carefully interpreted within linguistic constraints. Theoretically, this study underscores the necessity of integrating linguistic analysis into Qur’anic interpretation to ensure precise meaning extraction. Contribution: this research highlights the role of Arabic syntactic principles in shaping Islamic hermeneutics and provides a methodological framework for analyzing linguistic structures in Qur’anic studies.